FREQUENCY, THE CLINICAL AND BIOCHEMICAL FEATURES OF ACUTE DECOMPENSATED EPISODE WITH BETAKETOTHIOLASE DEFICIENCY IN VIETNAM NATIONAL CHILDREN'S HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objective: Frequency, the clinical and biochemical features acute decompensated episode with betaketothiolase deficiency.Subject and Method: A Descriptive study, 75 childrens beta-ketothiolase deficiency were diagnosed,treated and monitored in the Vietnam National Children’s Hospital from January 2015 to June 2021.Results: 92% of patients had acute decompensated episode, the age of onset was mainly less than12 months, on average, one patient had 1.5 ± 1.27 acute attacks. Common clinical features arerespiratory tract inflammation such as fever (91.3%), cough (53.6%), vomiting (73.9%) and thengo into mental disorder (97,1%). Biochemical characteristics: 97,1% of patients had ketonuriaduring acute decompensation episodes, the majority of patients with metabolic acidosis accountedfor 88,4%. Plasma acyl-carnitin profile revealed increased C5: 1 accounted for 82.6%, increasedC5: OH accounted for 86.9%. Urinary organic acids profile revealed mainly increased by 2M3HB,accounting for 79,7%.Conclusion: The frequency of acute decompensation accounted for 92%. Most patients hadsymptoms of respiratory infection such as fever, cough, then coma, plasma acyl-carnitin profilerevealed increased C5: 1 and C5: OH. Urinary organic acids profile revealed mainly increased by2M3HB.
Keywords: Beta-ketothiolase deficiency, C5: OH (tiglylcarnitine), C5:1(2-methyl- 3hydroxybutyrylcarnitine), 2MAA (2-methylacetoacetyl), 2M3HB (2-methyl-3-hydroxylbutyryl), TIG (tiglylcarnitine).